2014
DOI: 10.5114/wo.2014.43492
|View full text |Cite
|
Sign up to set email alerts
|

The clinical usefulness of assessing the concentration of cell adhesion molecules sVCAM-1 and sICAM-1 in the serum of women with primary breast cancer

Abstract: Aim of the studyAssessment of the concentrations of the soluble forms of the cell adhesion molecules sVCAM-1 and sICAM-1 in serum of female breast cancer patients. These concentrations were assessed in relation to factors such as: age, clinical stage of disease, histological grade of malignancy, the status of the local axillary lymph nodes, and the size of the primary tumour.Material and methodsA total of 103 patients with primary breast cancer, aged 29 to 89 years, were investigated. The control group consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Moreover, as concerned with the levels of serum VCAM-1, in a study by Pasieka et al [ 49 ], significantly higher levels of VCAM-1 were observed in the serum samples of only anaplastic thyroid carcinoma patients, while in PTC patients the circulating VCAM-1 levels were comparable with those of healthy control group. The increased levels of VCAM-1 in the peripheral blood have also been demonstrated in progression of many forms of cancer: non-small-cell lung cancer [ 50 ], breast cancer [ 17 , 51 ], rectal cancer [ 52 ], gastric cancer [ 53 , 54 ], colorectal cancer [ 55 59 ], prostate cancer [ 60 ], bladder cancer [ 61 ], urological malignancies [ 62 ], head and neck cancer [ 63 ], pancreatic cancer [ 64 ], and ovarian cancer [ 65 ]. Recently, Martinez et al [ 66 ] have reported higher levels of VCAM-1 in the bone marrow of advanced breast cancer patients than the healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as concerned with the levels of serum VCAM-1, in a study by Pasieka et al [ 49 ], significantly higher levels of VCAM-1 were observed in the serum samples of only anaplastic thyroid carcinoma patients, while in PTC patients the circulating VCAM-1 levels were comparable with those of healthy control group. The increased levels of VCAM-1 in the peripheral blood have also been demonstrated in progression of many forms of cancer: non-small-cell lung cancer [ 50 ], breast cancer [ 17 , 51 ], rectal cancer [ 52 ], gastric cancer [ 53 , 54 ], colorectal cancer [ 55 59 ], prostate cancer [ 60 ], bladder cancer [ 61 ], urological malignancies [ 62 ], head and neck cancer [ 63 ], pancreatic cancer [ 64 ], and ovarian cancer [ 65 ]. Recently, Martinez et al [ 66 ] have reported higher levels of VCAM-1 in the bone marrow of advanced breast cancer patients than the healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of VCAM-1 has been demonstrated on endothelial cells, macrophages, dendritic cells, and surface of cancer cells. The expression of VCAM-1 is known to increase under the influence of proinflammatory cytokines [ 17 ]. The cell-cell adhesion leads to clustering of VCAM-1 and the cytoplasmic domain of this clustered VCAM-1 particularly activates Ezrin which in turn activates the PI3K/AKT signaling that suppresses apoptosis and promotes survival signal in the tumour cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell adhesion molecules (CAM) including the epithelial cell adhesion molecule (EpCAM), VCAM1, ALCAM and ICAM1 have been implicated with clinical significance and prognostic factors in patients with several cancers, such as breast, ovarian and lung cancer ( Karabulut et al ., 2014 ; Kotteas et al ., 2014 ; Lee, 2014 ). In particular, the sICAM1 level in serum of the lung and breast cancer patients is correlated to the cancer stage and its aggressiveness degree ( Schroder et al ., 2011 ; Thielemann et al ., 2014 ). It was reported that ICAM1 is highly expressed in triple negative breast cancers (TNBC) cells compared to the non-TNBC and normal cells ( Guo et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high expression rate of sICAM-1 in breast cancer patients is associated with tumors at advanced stages and with those with the estrogen receptor negative phenotype [27] and the level of sICAM-1 in the serum of women with breast cancer was significantly higher than that observed in the serum of healthy women. They also found significant differences in sICAM expression between women with metastases to the axillary lymph nodes and women with no metastasis [28]. sICAM-1 concentrations increased in serum of breast cancer patients, and their levels seem to be related to poorer therapy response and prognosis [29].…”
Section: Discussionmentioning
confidence: 99%